Synthesis, Characterization and In Silico Study of Fe(III) Complex with N'-(4-Chlorobenzoyl)-Isonicotino-Hydrazide as Anti Tuberculosis Candidate - Ruswanto Ruswanto; Fajar Setiawan; Nur Rahayuningsih; Richa Mardianingrum; Nur Laili Dwi Hidayati; Elsi Eryanti (Jurnal Kimia Valensi, 2020)
The synthesis of Fe(III) complexes with ligands N'-(4-Chlorobenzoyl)isonicotinohydrazide can be synthesized through mixing metal and ligand dissolved in ethanol by reflux at ± 75oC for 5 hours. The instruments for the characterization of the complex were used UV-Visible and Infrared Spectrophotometry. The aims of the study are: to determine the synthesis method, characterize of the complex, and to study the interaction of the complex with target receptors. The weight of the synthesized compound was obtained by 38.1 mg. The purity of the complex has been tested using the determination of melting point and got a melting point range was 196-198oC. The maximum wavelength of Fe(III)N'-(4-Chlorobenzoyl)isonicotinohydrazid) complex was  261.0 nm and provide absorption of Fe-O vibrations at wavenumbers 530.42 cm-1. The docking process was done using AutodockTools-1.5.6 software which shows that the Fe(III)N'-(4-Chlorobenzoyl) isonicotinohydrazide complex can interact with Enoyl-Acyl Carrier Protein Reductase from Mycobacterium Tuberculosis and it has better  interaction than isoniazid or N'-(4-Chlorobenzoyl)isonicotinohydrazide compound with the acquisition of free energy binding (ΔG) -9.80 kcal/mol and inhibition constant (Ki ) 0.06529 μM.